“What are you doing here?”: Narratives of border crossings among diverse Afghans going to the UK at different times - López, María; Ryan, Louise (Frontiers in Sociology, 2023)
Through the “hostile environment” migration policy, the UK government has expressed its commitment to do whatever possible to deter and expel unwanted migrants. Faced with the loss of power in the context of globalization, the Conservative administration, elected in 2010, presented itself as a guarantor of citizens' security. The political discourse of “taking back control” of the nation's borders has resulted in increasingly restrictive immigration and asylum policies. In this paper, we present narratives of Afghans who arrived in the UK at different times and through different routes. As well as those evacuated from Kabul airport in 2021, we also interviewed participants who traveled via insecure routes over land and sea often taking months, or even years, and involving expensive people smugglers. While the evacuation from Kabul was a very public and highly reported event, often with celebratory tones in the international media as Western governments sought to “rescue” Afghan allies, those Afghans who travel to the UK via illegal routes are often stigmatized; demonized in press and political discourses. Building on the emerging body of literature that uses “journey as a narrative device” and drawing upon our novel dataset, we analyze how diverse migrants tell their stories and present agency, within contexts of extreme hazards, to achieve their imagined future. Moreover, applying a spatio-temporal lens we advance understanding of the intersection of place and time in how Afghans traveling to the UK, including recent evacuees, are framed differently with resultant consequences for how border crossings are negotiated and narrated. In so doing, we complicate simplistic categories of deserving vs. undeserving, genuine vs. fraudulent, evacuees vs. irregularised migrants.